Pengaruh Disiplin Kerja dan Motivasi terhadap Kinerja Pegawai dengan Variabel Intervening Kepuasan Kerja - Selfania, Fenni; Thamrin, Kemas Muhammad Husni; WK, Wita Farla (SAFE-Network, 2024)
This research aims to determine the effect of work discipline and motivation on employee performance with job satisfaction as an intervening variable among the staff of the Faculty of Medicine at Sriwijaya University. The sample in this study consists of BLU employees at the Faculty of Medicine, Sriwijaya University. The total sample consists of 108 people using the questionnaire data collection technique, and the method used is the Likert scale. The analysis method in this study uses the structural equation model (SEM). The results of this study indicate that work discipline and work motivation have a positive and significant effect on job satisfaction. Work discipline and work motivation have a positive and significant effect on job satisfaction. Employee performance has a positive and significant effect on job satisfaction. Work discipline and work motivation have a positive and significant effect on job satisfaction through employee performance.